Progress in Powder Based Additive Manufacturing - Drummer, Dietmar; Schmidt, Michael (Springer, 2025)
This open access book presents 12 years of cutting-edge research on additive manufacturing (AM), with a focus on innovative powder- and beam-based techniques. Developed through the Collaborative Research Center 814 at Friedrich-Alexander-Universität Erlangen-Nürnberg, it explores the use of laser and electron beams in transforming metal and polymer materials. From advanced strategies for selective laser melting to mesoscopic simulations of beam melting processes, this book offers a deep dive into the science behind AM. Key topics include the development of lightweight composite materials, efficient multi-material manufacturing, and optimal design of multifunctional hybrid components. Readers will also discover pioneering approaches to selective electron beam melting, reactive liquid systems for plastics, and tailored material characterization techniques. In addition, the book explores macroscopic modeling and geometric testing methods, offering new insights into the future of AM technologies. By combining theoretical advancements with practical applications, this volume serves as an essential resource for researchers and professionals in the field of additive manufacturin
Keywords: Additive Manufacturing Research; Powder and Beam AM; Metal and Polymer Additive Manufacturing; Laser Electron Beam Manufacturing; Functional Polymer Materials AM; Gas-Phase Powder Modification; Laser Beam Melting Research; Selective Laser Melting Composites; Electron Beam Melting Strategies; Laser Melting Plastics; Mesoscopic Simulation Additive Manufacturing; Hybrid Components Additive Manufacturing; Multi-Material Additive Manufacturing; Reactive Liquid Systems in AM; Hybrid Lattice Design AM; Macroscale Modeling Selective Melting; Additive Manufacturing Measurement Techniques; Metallic Components AM Simulation; Open Access